2019
DOI: 10.3390/app9234991
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Ground Vibration Analysis Based on a Three-Dimensional Coupled Train-Track-Soil Interaction Model

Abstract: A novel three-dimensional (3D) coupled train-track-soil interaction model is developed based on the multi-body simulation (MBS) principle and finite element modeling (FEM) theory using LS-DYNA. The novel model is capable of determining the highspeed effects of trains on track and foundation. The soils in this model are treated as saturated media. The wheel-rail dynamic interactions under the track irregularity are developed based on the Hertz contact theory. This model was validated by comparing its numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The 3D coupled train-track-soil interaction model has been validated in previous studies, and the validation results can be found from [4] and [5].…”
Section: Smmmentioning
confidence: 99%
See 2 more Smart Citations
“…The 3D coupled train-track-soil interaction model has been validated in previous studies, and the validation results can be found from [4] and [5].…”
Section: Smmmentioning
confidence: 99%
“…Train-induced ground vibrations can negatively affect surrounding residents, buildings, tunnels, drainage systems, overhead wiring structures, and so on [4,5,34,35,36]. Effective and efficient vibration mitigation solutions are desperately needed for high speed rail networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on dynamic amplification factors, geological condition, and the mitigating locations, the attenuation methods can be classified into three categories, including: (i) mitigating vibrations at the source, (ii) attenuating vibration intensity in the propagation path, and (iii) isolating the receiver such as surrounding structures from vibrations [5,6]. Compared with the other two types of mitigation methods (i.e., methods (i) and (ii)), it is rather difficult and often cost-consuming to build a vibration isolation system or to change the foundation condition under the existing buildings or infrastructures [7][8][9][10]. Therefore, the vibration mitigations at the source or at the transmission path are preferable to be applied in practice.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is not useful while considering track irregularities. Furthermore, a lot of FEM based parametric studies have been carried out to investigate the effect of moving load under different track and ground conditions [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%